1991
DOI: 10.1177/154079699101600404
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Role of Employers in Supported Employment

Abstract: Since the Workforce 2000 report documenting labor trends and issues was released by the Hudson Institute in 1987, business and industry have been reevaluating how support is provided to employees. Employee assistance programs, renewed investment in training, and other accommodations for an increasingly diverse workforce present an unparalleled opportunity to bring supported employment technology, values, and systems to contemporary business. This paper is an initial attempt at reconceptualizing supported emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…At the same time, remarkable innovations have emerged that have improved the basic notions of supported employment (Bloom, 1993;Fabian & Leucking, 1991;Hagner & Dileo, 1993;Nisbet, 1992;Rhodes, Sandow, Mank, Buckley, & Albin, 1991;. Natural supports in the workplace (e.g., Murphy, Fisher, & Rogan, 1992), assistive technology (e.g., Employment Network, 1992;Enders & Hall, 1990; Sowers & Powers, 1991), person-centered and career planning processes (Allen, 1989;Forest & Pearpoint, 1992;Mount, 1992;Mount, Beeman, & Ducharme, 1988), and a focus on choice and self-determination (e.g., Rehabilitation Act Amendments of 1992; West & Parent, 1992) have all enhanced the promise and the potential of supported employment.…”
mentioning
confidence: 99%
“…At the same time, remarkable innovations have emerged that have improved the basic notions of supported employment (Bloom, 1993;Fabian & Leucking, 1991;Hagner & Dileo, 1993;Nisbet, 1992;Rhodes, Sandow, Mank, Buckley, & Albin, 1991;. Natural supports in the workplace (e.g., Murphy, Fisher, & Rogan, 1992), assistive technology (e.g., Employment Network, 1992;Enders & Hall, 1990; Sowers & Powers, 1991), person-centered and career planning processes (Allen, 1989;Forest & Pearpoint, 1992;Mount, 1992;Mount, Beeman, & Ducharme, 1988), and a focus on choice and self-determination (e.g., Rehabilitation Act Amendments of 1992; West & Parent, 1992) have all enhanced the promise and the potential of supported employment.…”
mentioning
confidence: 99%
“…The topic of quality and the practices used to improve quality has become popular in the employment services literature (Albin, 1992;O'Brien, 1990;Rhodes, Sandow, Mank, Buckley, & Albin, 1991;Sandow, Rhodes, Mank, Ramsing, & Lynch 1990). The authors noted above draw heavily from the work of W. E. Deming and T. E. Gilbert and from efforts made by leaders in business and industry as they strive to improve quality, productivity, and profits.…”
Section: A Focus On Qualitymentioning
confidence: 98%
“…A number of authors now suggest that job coaches, who typically provide the social and job supports to employees with disabilities, may hinder the natural process of social integration for persons with disabilities in the workplace (Hagner, 1989;O'Brien & O'Brien, 1992). Conversely, it has been suggested that the role of co-workers without disabilities in work settings is important to improving the acceptance and integration of employees with disabilities (Callahan, 1992;Nisbet & Hagner, 1988;Olson & Sandow, 1991;Rhodes, Sandow, Mank, Buckley, & Albin, 1991;Shafer, 1986).…”
mentioning
confidence: 96%